Knowledge of Betel Chewers as a Predictor of Periodontal Disease - Imran, Herry; Niakurniawati, Niakurniawati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Oral health is essential for overall well-being, as poor dental and oral conditions can interfere with speech, mastication, and aesthetics. In Aceh, the habit of betel chewing is common and may contribute to periodontal disease. This study aimed to determine the association between public knowledge among betel chewers and periodontal disease. This analytic study employed a cross-sectional design conducted in Baroh Village, Montasik Subdistrict, Aceh Besar. Data were collected through questionnaire-based interviews and periodontal examinations. A total of 34 respondents were included using total sampling. Data were analyzed using the Chi-square test. Of the 34 respondents, 23.5% had good knowledge and 76.5% had poor knowledge. Periodontal conditions included 26.5% with calculus, 64.7% with shallow pockets, and 8.8% with deep pockets. The analysis showed a significant association between knowledge and periodontal disease (p = 0.001). The findings indicate that knowledge among betel chewers serves as a significant predictor of periodontal disease, where lower knowledge is associated with greater occurrence and severity.Keywords: knowledge; betel chewing; periodontal disease; predictor; community